O músico alternativo do centro histórico de joão pessoa: novos agentes, outros sujeitos - Borges, Sam Thiago Pereira (2016)
This PhD thesis analyses the process of construction of alternative musician subjects who act in the Antenor Navarro Square, located in the Historic Center of João Pessoa/PB (Brazil), through the social interactions established between them and Information and Communication Technologies (ICT). We advocate that the social interactions allowed by the ICT generate a musician subject in an ongoing process of deterritorialisation and reterritorialisation, with the working capacity of making music and the political condition altered by the possibility of manipulating the music structure. Therefore, it is seen the possibility of generating a sufficiently strong tension capable of affecting more consolidated instances of music production, promotion and distribution in the Phonographic Industry, affecting them on a scale that goes from the micro relations established through the web to the more traditional relations – such as those experienced in the Square. These observations were possible through the study of artistic trajectories of five artists in the alternative culture that operate in the Historic Center of João Pessoa end who envision the cyberspace as a locus of experimentations, shared experiences, and cheap and quick means of promotion. Through the life histories of the musicians, we tried to demonstrate how they travel between the Network and Antenor Navarro Square to give vent to their political actions. They are new agents, since they negotiate culture through their music labor. They are, as well, different musicians, since they are autonomous and connected to the digital structure of their object.